Cyanidin-3-O-glucoside reduces nanopolystyrene-induced toxicity and accumulation: roles of mitochondrial energy metabolism and cellular efflux. Issue 7 (17th June 2022) - Chen, Wen; Ye, Xiang; Tang, Qiong; Yu, Ting; Tu, Pengcheng; Zheng, Xiaodong
Abstract : C3G reduces polystyrene nanoplastic toxicity to different models, by which C3G-mediated energy metabolism improved the activity of ABC transporters and cellular efflux of polystyrene. Abstract : Nano-plastic pollution has been increasingly recognized as a key environmental issue. Nano-plastic exposure is linked to a multitude of environmental and health effects, and we have previously reported that cyanidin-3- O -glucoside (C3G) promoted discharge and reduced the biotoxicity of polystyrene (PS). This study further determines the impact of C3G on PS exposure, and investigates the role of energy metabolism in the ameliorative effects of C3G. Through a Caenorhabditis elegans ( C. elegans ) model, C3G was discovered to be capable of promoting discharge and alleviating biotoxicity induced by environment-relevant PS exposure. C3G was also found to restore PS-induced ATP reduction accompanied by improved mitochondrial dysfunction, suggesting involvement of energy metabolism. Using a Caco-2 cell model, we found that the molecular mechanism involves C3G protecting against PS-induced ATP reduction by activating the AMPK/SIRT1/PGC-1α signaling pathway. C3G-mediated ATP production and mitochondrial functions, which improve the activity of ABC transporters and cellular efflux of PS, may constitute the primary toxicity-alleviating mechanism through which C3G acts. Furthermore, in a mouse model administered with PS, it was discovered that C3G activates the AMPK/SIRT1/PGC-1α signaling pathway regulating the ATP level in colon tissue, in addition to the increased fecal PS discharge. These findings suggest that C3G protects against adverse effects of PS exposure on multiple organism models, and the underlying mechanism involves mitochondria-related energy metabolism and efflux.